Pengaruh Opini Audit dan Audit Delay Pada Auditor Switching dengan Karakteristik Komite Audit Sebagai Pemoderasi - Dwiphayana, Gusti Ngurah Made; Dharma Suputra, I Dewa Gede (E-Jurnal Akuntansi, 2019)
This study aims to examine the effect of audit opinion and audit delay on auditor switching and how the characteristics of the audit committee are able to moderate the influence of audit opinion and audit delay on auditor turnover. Determination of sample using purposive sampling method with samples of 120 companies. The data analysis technique used is logistic regression analysis and Moderated Regression Analysis (MRA). The results of the study show that audit opinion has a negative effect on auditor turnover, while audit delay has a positive effect on auditor turnover. The characteristics of the audit committee are able to weaken the positive influence of audit delay on auditor switching. But the characteristics of the audit committee are not able to moderate the influence of the audit opinion on the auditor switching. Keywords : Audit opinion, audit delay, audit committee, auditor switching.